Political leader's speech to the P.N.M. General Council on Sunday, May 4, 1975 - Williams, Eric ([PNM Publishing Company] Port of SpainTT, 1975)
Presents the views of Dr. Eric Williams, Political leader of the PNM and Prime Minister of Trinidad and Tobago on the PNM relations, and policies on the subject of Caribbean integration and the Caribbean Community.